2020
DOI: 10.1080/23802359.2019.1704642
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the endangered freshwater fish Microphysogobio rapidus (Cypriniformes, Cyprinidae) from Korea

Abstract: Microphysogobio rapidus is an endangered freshwater fish from Korea with a limited distribution in the Nakdong River. Here, we determined the mitochondrial genome of M. rapidus, which consisted of 16,603 bp with 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNA genes, and a control region (D-loop). The overall base composition of the complete genome was 29.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The following supporting information can be downloaded at: , Figure S1: Time tree of Huigobio and its close relatives based on 13 protein-coding genes of mitochondrial genomes; Table S1: Reviews of the genetic diversity of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S2: Reviews of the phylogeographical patterns of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S3: Primers and annealing temperature used in PCR amplification of mitochondrial genomes; Table S4: Sampling localities and source of mitochondrial genome for Huigobio and outgroup taxa; Table S5: Comparisons among six models of biogeography analyses in ancestral area reconstruction of H. chenhsienensis . References [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 26 , 27 , 37 , 65 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figure S1: Time tree of Huigobio and its close relatives based on 13 protein-coding genes of mitochondrial genomes; Table S1: Reviews of the genetic diversity of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S2: Reviews of the phylogeographical patterns of freshwater fishes endemic to southern China revealed by mitochondrial genes; Table S3: Primers and annealing temperature used in PCR amplification of mitochondrial genomes; Table S4: Sampling localities and source of mitochondrial genome for Huigobio and outgroup taxa; Table S5: Comparisons among six models of biogeography analyses in ancestral area reconstruction of H. chenhsienensis . References [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 26 , 27 , 37 , 65 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…Obtaining such data will be crucial for the development of a systematic conservation strategy, which is urgently required to safeguard the future of this species. Despite a few molecular phylogenetic studies, the lack of efficient molecular markers and comprehensive population genetic studies has hindered the comprehensive evaluation of the genetic diversity and genetic structure of this species [8,[12][13][14][15][16]. DNA fingerprinting analysis, including the utilization of microsatellite markers, is a widely used molecular method for evaluating genetic variability in natural populations, including endangered fish species [17,18].…”
Section: Introductionmentioning
confidence: 99%